Les systèmes experts : mythe ou réalité ? - Charette, Richard (Assurances)

(untitled) (HEC Montréal, 1993)
Since the information revolution, managers and administrators have recognized the value of information technologies as powerful tools to distribute data in the organization. This is especially true in the insurance industry where data and information are important assets. Two other essential assets, knowledge and expertise, can also be distributed efficiently by integrating expert systems in the organization's toolbox of applications. But this integration is not as easy as one may think. In fact managers and administrators are often either too optimistic or too pessimistic regarding the integration of expert systems in their organizations. These unrealistic expectations contribute to the failure of this technology in the marketplace. The following paper is intended to provide the reader with a clear and concise understanding of expert systems and their applications in the financial and insurance industry. Its purpose is also to demystify the technology so that managers can objectively appreciate the real value of expert systems.